City Reputation Indicators (CRIs): measuring inhabitants' city representation / Indicadores de Reputación Urbana: midiendo la representación de una ciudad en sus habitantes. Issue 1 (2nd January 2019) - Bonaiuto, Marino; Ariccio, Silvia; De Dominicis, Stefano; Fornara, Ferdinando; Molinario, Erica; Troffa, Renato; Wang, Haoxing
Abstract: Reputation is a socially mediated form of knowledge. In social psychology it has been studied with reference to different social actors (individuals, brands, cities, etc). However, the social-psychological conceptualization of city reputation lacks a consensual definition. This research aims to operationally define city reputation, via the construction and validation of the City Reputation Indicators (CRIs). The first and preliminary study ( N = 62) defines the underlying dimensions via six focus groups held in two Italian cities that differ in terms of their political/administrative and socio-demographic features. The second study ( N = 362) tests the properties of CRIs via a survey administered in Rome. Results show a first validation of the 12 CRIs' scales, which represent a basic tool for the assessment of people's perception of a city. Theoretical and applied implications are discussed, as well as development perspectives for improvements.